Myocardial creep and cardiorespiratory motion correction improves diagnostic accuracy of Rubidium-82 cardiac positron emission tomography - Lassen, Martin Lyngby; Rasmussen, Thomas; Byrne, Christina; Holmvang, Lene; Kjaer, Andreas; Hasbak, Philip (Journal of nuclear cardiology, 2023)
To evaluate the feasibility of retrospectively detecting and correcting periodical (cardiac and respiratory motion) and non-periodical shifts of the myocardial position (myocardial creep) using only the acquired Rubidium-82 positron emission tomography raw (listmode) data. This study comprised 25 healthy participants (median age = 23 years) who underwent repeat rest/adenosine stress Rubidium-82 myocardial perfusion imaging (MPI) and 53 patients (median age = 64 years) considered for revascularization who underwent a single MPI session. All subjects were evaluated for myocardial creep during MPI by assessing the myocardial position every 200 ms. A proposed motion correction protocol, including corrections for cardiorespiratory and creep motion (3xMC), was compared to a guideline-recommended protocol (StandardRecon). For the volunteers, we report test-retest repeatability using standard error of measurements (SEM). For the patient cohort, we evaluated the area under the receiver operating curve (AUC) for both stress and ischemic total perfusion deficits (sTPD and iTPD, respectively) using myocardial ischemia defined as fractional flow reserve values < 0.8 in the relevant coronary segment as the gold standard. Test-retest repeatability was significantly improved following corrections for myocardial creep (SEM; sTPD: StandardRecon = 2.2, 3xMC = 1.8; iTPD: StandardRecon = 1.6, 3xMC = 1.2). AUC analysis of the ROC curves revealed significant improvements for iTPD measurements following 3xMC [sTPD: StandardRecon = 0.88, 3xMC = 0.92 (P = .21); iTPD: StandardRecon = 0.88, 3xMC = 0.95 (P = .039)]. 3xMC has the potential to improve the diagnostic accuracy of myocardial MPI obtained from positron emission tomography. Therefore, its use should be considered both in clinical routine and large-scale multicenter studies. Evaluar la factibilidad de detectar y corregir retrospectivamente los cambios periódicos (movimiento cardíaco y respiratorio) y no periódicos de la posición del miocardio (deslizamiento del miocardio) utilizando solo los datos en crudo sin procesar (modo de lista) de la tomografía por emisión de positrones con Rubidio-82. Este estudio contó con 25 participantes sanos (mediana de edad = 23 años) que se sometieron a imágenes repetidas de perfusión miocárdica (MPI) con Rubidio-82 en protocolo reposo/estrés con adenosina y 53 pacientes (mediana de edad = 64 años) considerados para revascularización que se sometieron a un solo estudio de MPI. A todos los sujetos se les evaluó el deslizamiento del miocardio durante el MPI mediante la evaluación de su posición cada 200 ms. Un protocolo de corrección de movimiento propuesto, que incluye correcciones para movimiento cardiorrespiratorio y de deslizamiento (3xMC), se comparó con un protocolo recomendado por las guías (StandardRecon). Para los voluntarios, informamos la repetibilidad test-retest utilizando medidas estándar de error (SEM). Para la cohorte de pacientes, evaluamos el área bajo la curva operativa del receptor (AUC) tanto para el estrés como para los déficits de perfusión total isquémicos (sTPD y iTPD, respectivamente) usando isquemia miocárdica definida como valores de reserva de flujo fraccional < 0.8 en el segmento coronario relevante como el estándar dorado de referencia. La repetibilidad test-retest mejoró significativamente después de las correcciones para el deslizamiento del miocardio (SEM; sTPD: StandardRecon = 2.2, 3xMC = 1.8; iTPD: StandardRecon = 1.6, 3xMC = 1.2). El análisis AUC de las curvas ROC reveló mejoras significativas para las mediciones de iTPD después de 3xMC (sTPD: StandardRecon = 0.88, 3xMC = 0.92 (P = .21); iTPD: StandardRecon = 0.88, 3xMC = 0.95 (P = .039)). 3xMC tiene el potencial de mejorar la precisión diagnóstica del MPI miocárdico obtenido a partir de la tomografía por emisión de positrones. Por lo tanto, su uso debe ser considerado tanto en los estudios clínicos rutinarios como en estudios multicéntricos a gran escala. 本研究旨在评估使用铷-82正电子发射扫描获得的原始数据, 回顾性检测和校正心肌位置的周期性 (心脏和呼吸运动) 和非周期性变化 (心肌蠕变) 的可行性。 这项研究包括25名接受静息/腺苷负荷铷-82心肌灌注显像MPI的健康参与者 (中位年龄 = 23岁) ; 以及53名仅接受一次MPI拟行血运重建的患者 (中位年龄=64岁) 。我们通过每隔200毫秒评估心肌位置的手段来评估MPI期间的心肌蠕变。本研究比较包括心肺和蠕变运动校正的运动校正方案(3xMC) 与指南推荐的方案(StandardRecon) 。在健康参与者队列中, 我们使用标准测量误差SEM来报告重测信度。在患者队列中, 我们评估了负荷和缺血总灌注缺损(sTPD和iTPD) 的接收者操作特征曲线下面积AUC。心肌缺血的金标准被定义为有关冠状动脉段的血流储备分数< 0.8。 校正心肌蠕变后, 重测信度显著提高(SEM: sTPD: StandardRecon = 2.2, 3xMC = 1.8; iTPD: StandardRecon = 1.6, 3xMC = 1.2) 。AUC分析表明, 在3xMC校正后, iTPD的测量准确性显著提高(sTPD: StandardRecon = 0.88, 3xMC = 0.92(P = .21) ; iTPD: StandardRecon = 0.88, 3xMC = 0.95(P = .039) ) 。 运动矫正方案3xMC可提高PET-MPI诊断的准确性。因此, 在临床常规检查和大规模多中心研究中应考虑应用该方案。 La correction pour le mouvement cardio-respiratoire et le glissement myocardique améliore la précision diagnostique de la tomographie par émission de positrons cardiaque au Rubidium-82. Évaluer la faisabilité de détecter rétrospectivement et de corriger les changements périodiques (mouvements cardiaques et respiratoires) et non-périodiques de la position du myocarde (glissement myocardique) en utilisant seulement les données brutes (en mode liste) de la tomographie par positrons au Rubidium-82. L’étude incluait 25 volontaires sains (âge médian = 23 ans) qui ont eu des études répétées de perfusion myocardique (ÉPM) au Rubidium-82 repos-adénosine et 53 patients (âge médian = 64 ans) considérés pour revascularisation qui ont eu une seule séance de ÉPM. Tous les sujets ont été étudiés pour le glissement myocardique durant ÉPM en évaluant la position du myocarde chaque 200ms. Un protocole de correction de mouvement proposé, incluant les corrections pour les mouvements cardio-respiratoires et de glissement (3xMC), a été comparé au protocole recommandé par les lignes directrices (Recon.Standard). Pour les volontaires, nous rapportons la répétabilité test-retest en utilisant l’erreur standard des mesures (ESM). Pour la cohorte de patients, nous avons évalué la zone dérivée de la courbe de la fonction d’efficacité du receveur (ROC) pour les déficits à l’effort et les déficits de perfusion ischémiques totaux (respectivement sTPD et iTPD) en utilisant l’ischémie myocardique définie comme ayant une valeur de réserve de flot fractionnel < 0.8 dans un segment coronarien pertinent comme mesure étalon. La répétabilité test-retest était améliorée de façon significative après les corrections pour le glissement myocardique (ESM;sTPD : Recon.Standard = 2.2, 3xMC = 1.8, iTPD : Recon.Standard = 1.6, 3xMC = 1.2). L’analyse de la zone sous la ROC a révélé des améliorations significatives pour les mesures de iTPD après le 3xMC (sTPD : Recon.Standard = 0.88, 3xMC = 0.92 (P = .21) : iTPD : Recon.Standard = 0.88, 3xMC = 0.95 (P = .039)). Le 3xMC a le potentiel d’améliorer la précision diagnostique des ÉPM obtenues à partir de la tomographie par émission de positrons. Par conséquent, son utilisation devrait être considérée à la fois en routine clinique mais aussi dans des études multicentriques à grande échelle.